Sendai virus-mediated transduction of mammalian spermatogonial stem cells†. Issue 2 (25th August 2018) - Watanabe, Satoshi; Kanatsu-Shinohara, Mito; Shinohara, Takashi
Abstract: Spermatogonial stem cells (SSCs) provide the foundation of spermatogenesis. However, because of their small number and slow self-renewal, transfection of SSCs has met with limited success. Although several viral vectors can infect SSCs, genome integration and an inability to maintain long-term gene expression have hampered studies on SSCs. Here we report successful SSC infection by Sendai virus (SV), an RNA virus in the Paramyxoviridae. The SV efficiently transduced germline stem (GS) cells, cultured spermatogonia with enriched SSC activity, and maintained gene expression for at least 5 months. It also infected freshly isolated SSCs from adult testes. The transfected GS cells reinitiated spermatogenesis following spermatogonial transplantation into seminiferous tubules of infertile mice, suggesting that SV transfection does not interfere with spermatogenesis progression. On the other hand, microinjection of SV into the seminiferous tubules of immature mice transduced SSCs and Sertoli cells, but did not transduce Leydig or peritubular cells by interstitial virus injection. SV-infected hamster GS cells, and freshly isolated rabbit or monkey SSC-like cells were identified following xenogeneic spermatogonial transplantation, suggesting that SV transduces SSCs from several mammalian species. Thus, SV is a useful vector that can transduce both SSCs and Sertoli cells and overcome problems associated with other viral vectors. Abstract : Sendai virus can transduce spermatogonia without genome integration.